Hexakis(μ(2)-2-aminoethanethiolato)triiron(III) tris(perchlorate) - Igashira-Kamiyama, Asako (International Union of Crystallography, 2008)
In the title salt, [Fe(3)(C(2)H(6)NS)(6)](ClO(4))(3), the trinuclear cation lies on a special position of [Image: see text] site symmetry; the central Fe atom is coordinated by six thiolate groups from the two flanking fac-(S)-[Fe(C(2)H(6)NS)(3)] units. In the flanking units, the three C(2)H(6)NS groups each chelate to the metal atom. The cations interact with the perchlorate anions through weak N—H⋯O hydrogen bonds resulting in a three-dimensional network. In the asymmetric unit two cations are present, one of which is disordered over two positions with occupancies of 0.75 and 0.25.